The Intervention of Islamic Law on Minangkabau Tradition Regarding Children Adoption - Helmi Yusnita; Endri Yenti; Safrin Salam; Kayode Muhammed Ibrahim (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
The process of child adoption is not done widely based on The Traditional Law of Minangkabau because most of the adopted children are still their relative. The legal status of adopted child in the foster family can be obtained through the court where the status is the same with biological child or foster child, while the legal status of adopted child in the adopted relative can be gained through the tribe recognition or determination of Minangkabau Tradition namely as “kamanakan di bawah lutuik” (the closest nephew/niece). The purpose of this paper was to find out how was Islamic law intervention towards the law of Minangkabau tradition especially in child adoption. This research employed Field Research with the main data came from primary data obtained from informants in the field and the secondary data obtained from the materials related to the research. The data collection was carried out through interview, reading, and grouping in accordance with the theme being discussed, then were analyzed by using descriptive theory, inductive theory, and presented them in the form of paper. The results of this research state that in Islam and Minangkabau tradition basically forbid someone to adopt other people’s child by cutting the family ties with the child’s parents, then move it to the foster parents because it can cause chaos in the inheritance system either according to the traditional law or according to Islamic Law.